DYNAMIC REANIMATION FOR FACIAL PARALYSIS – A REVIEW - RATHISHREE; DR. M.P.SANTHOSH KUMAR (International Journal of Pharma and Bio Sciences, 2015)
Facial nerve paralysis is a relatively common condition of the seventh cranial nerve affecting the population, causing esthetic, functional and psychological problems. With the advancement of technology many surgical techniques have been developed for treating patients with facial palsy. This article reviews about the surgical techniques in the management of patients with facial palsy for smile reconstruction. Also, it discusses about the etiology and clinical features of facial palsy, anatomy of smile, goals of reanimation, choosing the appropriate surgical option based on patient’s condition and its outcomes.